EDUKASI PENTINGNYA MENGKONSUMSI PROBIOTIK SEBAGAI UPAYA PENCEGAHAN TERJADINYA DYSBIOSIS DI KELURAHAN SETIARATU KOTA TASIKMALAYA - Nunung Yulia; Shandra Isasi Sutiswa; Irvan Herdiana (Poltekkes Kemenkes Tasikmalaya, 2023)
Dysbiosis is a condition where there is an imbalance in the number of microorganisms in the human digestive tract. Basically, in normal conditions, colonies of microorganisms tend to act as normal flora that helps the process of nutrition digestion and maintain the immune system. However, when the number of colonies increases significantly, the body will begin to experience various diseases symptoms. The occurrence of dysbiosis in the end will be able to cause systemic abnormalities, such as interference with the absorption of nutrients that potentially cause metabolic abnormalities. Probiotics are live microorganisms which when administered in appropriate doses will benefit the health of the host. The ability of probiotics in symbiosis with microorganisms that exist in the intestine can suppress the growth rate of harmful bacteria (pathogens), and in the end will be able to improve the immune system. Setiaratu area is an area that borders the location of Tasikmalaya Ministry of Health Poltekkes. In this community service, outreach activities and creation of leaflets about the importance of probiotics consumption as an effort to prevent the occurrence of dysbiosis has been conducted in the district of Setiaratu. This community service was carried out in conjunction with Community Service Program of Poltekkes Kemenkes Tasikmalaya. After this PKM activity, it is hoped that the public can be expected to increase knowledge about dysbiosis and the use of probiotics to prevent and curative dysbiosis, especially in Setiaratu area.